Peripheral T-cell lymphoma: Frequency and distribution in a tertiary referral center in South India - Deepak K Burad; Manipadam M Therese; Sheila Nair (Wolters Kluwer Medknow Publications, 2012)
Background and Aim: Peripheral T/NK-cell lymphomas are uncommon types of non-Hodgkin's lymphoma (NHL) with a higher frequency in Far East countries as compared to the West. This study was undertaken to ascertain the frequency and distribution pattern of peripheral T-cell lymphomas (PTCLs) diagnosed in a tertiary care center in South India. Materials and Methods: This retrospective study was carried out in Department of General Pathology, Christian Medical College, Vellore. The time period was for 2 years from 1 st January 2008 till 31st December 2009. All PTCLs were reviewed and classified according to the World Health Organization (WHO) 2008 classification. Results: Of a total of 1032 cases of NHL, 180 cases were PTCL, which accounted for 17.4% cases of all the NHLs. Of these, PTCL, not otherwise specified (PTCL, NOS) was the most common subtype (48 cases, 26.1%), followed by anaplastic large cell lymphoma (41 cases, 22.8%), mycosis fungoides (21 cases, 11.7%), angioimmunoblastic T-cell lymphoma (16 cases, 8.9%), subcutaneous panniculitis like T-cell lymphoma (15 cases, 8.4%), extranodal NK/T-cell lymphoma, nasal type (12 cases, 6.7%), and hepatosplenic T-cell lymphoma (10 cases, 5.6%). The most common primary site of presentation was nodal accounting for 42% followed by cutaneous (34%), upper aerodigestive sites (8.9%), spleen (6.7%), and gastrointestinal tract (GIT; 3.3%). Conclusions: This is the largest single study on PTCLs in India and we document that its frequency is higher than that reported in Western literature and previous Indian studies and almost similar to that reported in some Far East studies. The frequency of mycosis fungoides, subcutaneous panniculitis like T-cell lymphoma, and hepatosplenic T-cell lymphoma was higher than that reported in the World literature and previous Indian studies. The frequency of extranodal NK/T-cell lymphoma and angioimmunoblastic T-cell lymphoma was much lower than that reported in the Far East literature.